Overview of multi-wavelength laser generation techniques - Ismail A.; Sulaiman A.H.; Jamaludin M.Z.; Abdullah F. (Mattingley Publishing, 2023)
Brillouin scattering; Comb filters; Dense wavelength division multiplexing; Waveguide filters; Cascaded modulators; Device testing; Multi-wavelength lasers; Multi-wavelengths; Single source; Arrayed waveguide gratings